Impacts of high-speed railways on economic growth and disparity in China. (August 2020) - Jin, Mengjie; Lin, Kun-Chin; Shi, Wenming; Lee, Paul T.W.; Li, Kevin X.
Highlights: We empirically test economic impacts of China's high-speed railways (HSRs) network. Our spatial econometric model confirms that HSR drives local economic growth. However, the spill-over effect is insignificant. HSR significantly increases growth in large-mega cities and developed cities. However, it could widen economic disparity in China. Abstract: China's high-speed railways (HSRs) networks have dramatically expanded since 2008, which is widely believed to have promoted economic growth. This study empirically tests this hypothesis and analyses the impact of HSRs on economic disparity between 2002 and 2016 in China using a spatial econometric model. The results confirm the role of HSRs as a driving force in promoting local economic growth, although the spill-over effect is found to be insignificant. However, the cross-city analysis suggests there are heterogeneous effects of HSRs on economic growth. By dividing the sample into small-medium cities and large-mega cities, as well as least-developed, developing, and developed cities, this study finds that HSRs make a significant positive contribution to economic growth in large-mega cities and developed cities but has insignificant effects in other cities. The results indicate that HSRs can widen economic disparity in China. Our findings not only advance the understanding of the role of HSRs in promoting China's economic growth but also provide insights for planning future HSR networks. This study concludes that each city should reasonably plan its HSR network to promote economic growth and reduce economic disparity by accounting for different resource endowments, especially geographic and population factors.